Evaluation of Compressive Strength of Concrete with Replacement of Conventional Coarse and Fine Aggregates Using Palm Kernel Shell and Coconut Husk - Kamil, Firmanilah; Purnomo, Julyan (Universitas Muhammadiyah Surakarta, 2024)
Concrete is a widely used construction material, but its production has a negative impact on the environment. This study aims to determine the effect and optimal percentage of using palm kernel shells and coconut fiber in concrete mixtures on the compressive strength of concrete. The research method involved making a variety of concrete mixes with the replacement of conventional aggregates by palm kernel shells as coarse aggregate and coconut fiber as fine aggregate. Four mix variations were tested: A (1% coconut fiber, 5% palm kernel shell), B (2% coconut fiber, 5% palm kernel shell), C (1% coconut fiber, 10% palm kernel shell), and D (2% coconut fiber, 10% palm kernel shell). Compressive strength testing was conducted at 7, 14, and 28 days of concrete age. The analysis showed that variation A, with 1% coir and 5% palm kernel shell, produced the closest compressive strength to normal concrete. ANOVA tests confirmed the significant effect of these mixtures on compressive strength. The contribution of this research lies in the development of alternative concrete materials that are more environmentally friendly, utilizing agricultural waste to reduce dependence on natural resources and lower the carbon footprint of the construction industry.